A dual center study to compare breath volatile organic compounds from smokers and non-smokers with and without COPD. (15th April 2016) - Gaida, A; Holz, O; Nell, C; Schuchardt, S; Lavae-Mokhtari, B; Kruse, L; Boas, U; Langejuergen, J; Allers, M; Zimmermann, S; Vogelmeier, C; Koczulla, A R; et al.
Abstract: There is increasing evidence that breath volatile organic compounds (VOC) have the potential to support the diagnosis and management of inflammatory diseases such as COPD. In this study we used a novel breath sampling device to search for COPD related VOCs. We included a large number of healthy controls and patients with mild to moderate COPD, recruited subjects at two different sites and carefully controlled for smoking. 222 subjects were recruited in Hannover and Marburg, and inhaled cleaned room air before exhaling into a stainless steel reservoir under exhalation flow control. Breath samples (2.5 l) were continuously drawn onto two Tenax ® TA adsorption tubes and analyzed in Hannover using thermal desorption-gas chromatography-mass spectrometry (TD-GC-MS). Data of 134 identified VOCs from 190 subjects (52 healthy non-smokers, 52 COPD ex-smokers, 49 healthy smokers, 37 smokers with COPD) were included into the analysis. Active smokers could be clearly discriminated by higher values for combustion products and smoking related VOCs correlated with exhaled carbon monoxide (CO), indicating the validity of our data. Subjects from the study sites could be discriminated even after exclusion of cleaning related VOCs. Linear discriminant analysis correctly classified 89.4% of COPD patients in the non/ex-smoking group (cross validation (CV): 85.6%), and 82.6% of COPD patients in the actively smoking group (CV: 77.9%). We extensively characterized 134 breath VOCs and provide evidence for 14 COPD related VOCs of which 10 have not been reported before. Our results show that, for the utilization of breath VOCs for diagnosis and disease management of COPD, not only the known effects of smoking but also site specific differences need to be considered. We detected novel COPD related breath VOCs that now need to be tested in longitudinal studies for reproducibility, response to treatment and changes in disease severity.